Presynaptic Inhibition Selectively Weakens Peptidergic Cotransmission in a Small Motor System - DeLong, Nicholas D. (American Physiological Society, 2009)
The presence and influence of neurons containing multiple neurotransmitters is well established, including the ability of coreleased transmitters to influence the same or different postsynaptic targets. Little is known, however, regarding whether presynaptic regulation of multitransmitter neurons influences all transmission from these neurons. Using the identified neurons and motor networks in the crab stomatogastric ganglion, we document the ability of presynaptic inhibition to selectively inhibit peptidergic cotransmission. Specifically, we determine that the gastropyloric receptor (GPR) proprioceptor neuron uses presynaptic inhibition to selectively regulate peptidergic cotransmission from the axon terminals of MCN1, a projection neuron that drives the biphasic (retraction, protraction) gastric mill (chewing) rhythm. MCN1 drives this rhythm via fast GABAergic excitation of the retraction neuron Int1 and slow peptidergic excitation of the lateral gastric (LG) protraction neuron. We first demonstrate that GPR inhibition of the MCN1 axon terminals is serotonergic and then establish that this serotonergic inhibition weakens MCN1 peptidergic excitation of LG without altering MCN1 GABAergic excitation of Int1. At the circuit level, we show that this selective regulation of MCN1 peptidergic cotransmission is necessary for the normal GPR regulation of the gastric mill rhythm. This is the first demonstration, at the level of individual identified neurons, that a presynaptic input can selectively regulate a subset of coreleased transmitters. This selective regulation changes the balance of cotransmitter actions by the target multitransmitter neuron, thereby enabling this neuron to have state-dependent actions on its target network. This finding reveals additional flexibility afforded by the ability of neurons to corelease multiple neurotransmitters.